DRIVERS OF STUDENTS’ LMS CONTINUANCE: USEFULNESS, EASE OF USE, ENGAGEMENT, AND SATISFACTION - Edi Suyitno; Agus Munandar (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines factors that drive students’ continuance intention to use a learning management system (LMS) in higher education by integrating Technology Acceptance Model (TAM) variables (perceived usefulness and perceived ease of use), student engagement, and learning satisfaction. Data were collected from 286 university students (280 provided complete demographic information) and analyzed using PLS-SEM with bootstrapping (5,000 subsamples). The results show that perceived usefulness significantly increases both learning satisfaction and continuance intention. Perceived ease of use significantly enhances learning satisfaction but does not directly influence continuance intention. Student engagement positively affects learning satisfaction and continuance intention, indicating that sustained LMS use is shaped not only by system perceptions but also by students’ learning involvement. Learning satisfaction significantly increases continuance intention. Overall, the model demonstrates strong explanatory power for learning satisfaction and continuance intention. These findings imply that universities should prioritize LMS features that deliver tangible learning benefits, reduce friction in use, and support engaging learning activities to foster students’ long-term willingness to continue using LMS-based learning.